2022
DOI: 10.1097/md.0000000000030967
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects PC12 cells from a high glucose-induced inflammatory response by regulating the miR-218-5p/TLR4 axis

Abstract: Background: Curcumin exerts a protective effect on diabetic encephalopathy (DN), It is known for its potent neuroprotective, anti-inflammatory, antioxidant, and anticancer properties. However, the underlying mechanisms of curcumin's neuroprotective effects resulting from high glucose (HG)-induced injuries remain unknown. The purpose of this study is to identify the protective mechanism of Curcumin in the DN.Methods: In this study, pheochromocytoma cells (PC12 cells) were pretreated with different concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…According to previous studies, there are many miRNAs involved in the treatment of different diseases by curcumin. Studies have shown that curcumin can attenuate vascular calcification through the exosomal miR-4b-92p/KLF3 axis [ 34 ], and curcumin therapy protects PC12 cells from high glucose-induced inflammatory responses by promoting the expression of miR-218-5p [ 35 ]. In this study, we found that miR-152-3p was highly expressed in DFU patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, there are many miRNAs involved in the treatment of different diseases by curcumin. Studies have shown that curcumin can attenuate vascular calcification through the exosomal miR-4b-92p/KLF3 axis [ 34 ], and curcumin therapy protects PC12 cells from high glucose-induced inflammatory responses by promoting the expression of miR-218-5p [ 35 ]. In this study, we found that miR-152-3p was highly expressed in DFU patients.…”
Section: Discussionmentioning
confidence: 99%